2005
DOI: 10.1523/jneurosci.0915-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Limited Segregation of Different Types of Sound Localization Information among Classes of Units in the Inferior Colliculus

Abstract: The auditory system uses three cues to decode sound location: interaural time differences (ITDs), interaural level differences (ILDs), and spectral notches (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 61 publications
5
40
0
Order By: Relevance
“…1C. On average, the first-spike latency variation contains 0.70 Ϯ 0.41 (SD) bits of information about the stimuli, somewhat less than the information in spike count or ongoing spike timing (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C. On average, the first-spike latency variation contains 0.70 Ϯ 0.41 (SD) bits of information about the stimuli, somewhat less than the information in spike count or ongoing spike timing (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for the design of these experiments is explained elsewhere (17,18). Two sets of 25 stimuli were used, varying in two binaural sound localization cues each.…”
Section: Resultsmentioning
confidence: 99%
“…Higher up in the auditory system, Chase and Young (2005) studied the coding of multiple cues for space in cat inferior colliculus (IC). The question they addressed was that of segregation of processing pathways through the IC.…”
Section: Applications To the Auditory Systemmentioning
confidence: 99%
“…The central nucleus of the inferior colliculus (ICC) receives ascending input from nearly every major brainstem nucleus (Roth et al, 1978;Adams, 1979;Brunso-Bechtold et al, 1981;Oliver et al, 1997) and is one of the first sites of convergence for the three major sound-localization cues: interaural level differences (ILDs), interaural timing differences (ITDs), and monaural spectral cues (SNs for spectral notches). Previous work has shown that single ICC neurons display a range of sensitivity to localization cues, and most of the neural responses are modulated by more than one cue (Benevento and Coleman, 1970;Caird and Klinke, 1987;Delgutte et al, 1995Delgutte et al, , 1999Chase and Young, 2005). This work, however, has all been based on the assumption of a rate code.…”
Section: Introductionmentioning
confidence: 97%
“…The analysis allows the time resolution of the temporal representation to be determined, suggesting that a temporal decoder would have to be sensitive to spike-timing coincidences of ϳ12 ms to extract maximum information. Temporal coding increases the degrees of freedom of the spike code in such a way that multiple stimulus features can be independently represented, which is not possible with only a rate code (Chase and Young, 2005).…”
Section: Introductionmentioning
confidence: 99%